1971
DOI: 10.1083/jcb.51.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Origin of Basal Lamina and Anchoring Fibrils in Adult Human Skin

Abstract: The purpose of this investigation was to study the formation and origin of basal lamina and anchoring fibrils in adult human skin . Epidermis and dermis were separated by "cold trypsinization ." Viable epidermis and viable, inverted dermis were recombined and grafted to the chorioallantoic membrane of embryonated chicken eggs for varying periods up to 10 days . Basal lamina and anchoring fibrils were absent from the freshly trypsinized epidermis before grafting although hemidesmosomes and tonofilaments of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(58 citation statements)
references
References 19 publications
3
55
0
Order By: Relevance
“…Classic studies using epidermal explants, viable and nonviable dermis, and chorioallantoic membrane concluded that the basal lamina is of epithelial origin (Briggaman et al, 1971). Another more recent study using human keratinocytes transplanted to athymic mice concluded that anchoring fibrils are of epithelial origin (Regauer et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Classic studies using epidermal explants, viable and nonviable dermis, and chorioallantoic membrane concluded that the basal lamina is of epithelial origin (Briggaman et al, 1971). Another more recent study using human keratinocytes transplanted to athymic mice concluded that anchoring fibrils are of epithelial origin (Regauer et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructurally, this basement membrane consists of an electron-lucent region, the lamina lucida, directly adject to the epithelial and myoepithelial cells, and an electron dense region, the lamina densa, located between the lamina lucida and the connective tissue (2). In some tissues anchoring fibrils that extend from the lamina densa into the surrounding connective tissue have been described (3). Several protein components of basement membranes have been identified (4).…”
mentioning
confidence: 99%
“…the epidermal basement membranes are thicker than Schwann cell basement membranes ( fig. 1a, e), and the former have anchoring filaments [Beerens et al, 1975;Cohn et al, 1977] and anchoring fibrils [Briggaman et al, 1971;Scaletta and MacCallum, 1974;Wasano and Yamamoto, 1985], which connect the lamina densa to the epithelial cells and underlying connective tissue, respectively. On the other hand, no distinct connecting structures are observed along the basement membranes of Schwann cells.…”
Section: Discussionmentioning
confidence: 99%